The Effect of Ice Cream Stick Learning Media on Multiplication Calculation Skills of Second Grade Students at UPT SPF SDI BTN IKIP 1, Rappocini District, Makassar City - Tati, Andi Dewi Riang; Salam, Siti Maulidina; Nurhaedah, Nurhaedah (Program Studi PGSD FIP UNM, 2024)
This study was conducted based on the problem identified at UPT SPF SDI BTN IKIP 1, Rappocini District, Makassar City, namely the low multiplication calculation skills of the students. The objectives of this study are: (1) to describe the use of ice cream stick learning media in Grade II at UPT SPF SDI BTN IKIP 1, Rappocini District, Makassar City; (2) to describe the multiplication calculation skills of Grade II students at UPT SPF SDI BTN IKIP 1, Rappocini District, Makassar City; and (3) to determine the effect of using ice cream stick learning media on the multiplication calculation skills of Grade II students at UPT SPF SDI BTN IKIP 1, Rappocini District, Makassar City. This research employed a quantitative approach using a quasi-experimental design. The research design used was the nonequivalent control group design. The independent variable in this study was the ice cream stick learning media, and the dependent variable was the students' multiplication calculation skills. The study involved two classes: the experimental class (II A) and the control class (II B), with the sampling technique used being purposive sampling. Data collection techniques included observation sheets and tests. The data collection procedure consisted of a pretest, treatment, and posttest, and the data were analyzed using descriptive and inferential statistical methods with the assistance of IBM SPSS Statistics software. The results of the study show that: (1) the learning activities using ice cream stick media were conducted effectively; (2) the multiplication calculation skills of students improved after being taught using the ice cream stick media, as indicated by significant differences between the experimental and control classes in terms of test scores and observation sheets. This was proven by the shift in student performance from the